Turning the Tables: Power Relations Between Consumer Researchers and Other Mental Health Researchers. (3rd August 2018) - Happell, Brenda; Gordon, Sarah; Bocking, Julia; Ellis, Pete; Roper, Cath; Liggins, Jackie; Scholz, Brett; Platania-Phung, Chris
Abstract: A crucial development resulting from consumer involvement in mental health services has been engagement as active participants in mental health research, often conducted in collaboration with mental health researchers representing the health disciplines (referred to in this paper as 'other' researchers). Despite progress in mental health consumer research, unequal power relations continue to pose a major barrier. Although power issues are discussed in the literature, there is little research from the perspective of other mental health researchers who have collaborated with consumers on research projects. This qualitative study explored other mental health researchers' perspectives on the role of power in collaborative research with consumers. Semi-structured interviews were completed with 11 other mental health researchers. Thematic analysis of the transcript version of interview recordings was conducted. The findings were grounded in 'the table' as a literal and metaphorical site of power relations. The umbrella theme was prominence and presence (of consumers) at the table, followed by subthemes on barriers ( tokenism, undermined potential ) and surmounting them through reworking power ( critical mass and openness to power dynamics ). Overall it was found that while there continue to be significant power-related barriers to further building of robust collaborative research with consumers in mental health, there are several avenues that should be considered, much more assertively, to disrupt and transcend them.